2016
DOI: 10.1007/s11274-015-1996-x
|View full text |Cite
|
Sign up to set email alerts
|

chr genes from adaptive replicons are responsible for chromate resistance by Burkholderia xenovorans LB400

Abstract: The chromate ion transporter (CHR) superfamily includes proteins that confer chromate resistance by extruding toxic chromate ions from cytoplasm. Burkholderia xenovorans strain LB400 encodes six CHR homologues in its multireplicon genome and has been reported as highly chromate-resistant. The objective of this work was to analyze the involvement of chr redundant genes in chromate resistance by LB400. It was found that B. xenovorans plant rhizosphere strains lacking the megaplasmid are chromate-sensitive, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Taken together, the ability of KJ-34 to protect against B. cinerea, combined with its ability to fix nitrogen, [can increase plant resistance] to pathogens and promote growth. Burkholderia bacteria have the ability to degrade environmental pollutants, B. xenovorans LB400 can decrease carcinogens (polychlorinated biphenyl, 2-aminophenol, Metallica) (Martıńez et al, 2007;Chirino et al, 2013;Reyes-Gallegos et al, 2016). The Burkholderia species MBA4 can enrich and bioremediate haloacids from soil (Su et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the ability of KJ-34 to protect against B. cinerea, combined with its ability to fix nitrogen, [can increase plant resistance] to pathogens and promote growth. Burkholderia bacteria have the ability to degrade environmental pollutants, B. xenovorans LB400 can decrease carcinogens (polychlorinated biphenyl, 2-aminophenol, Metallica) (Martıńez et al, 2007;Chirino et al, 2013;Reyes-Gallegos et al, 2016). The Burkholderia species MBA4 can enrich and bioremediate haloacids from soil (Su et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the first set of experiments, we compared the growth of the wildtype and recombinant strains under different levels of Cr stress. We wondered whether the accumulation of multiple Cr transporters in B. subtilis results in a more robust extrusion of Cr(VI), as is seen in some other species ( Reyes-Gallegos et al, 2016 ). Another issue we addressed was whether ChrA, an LCHR chromate transporter, compensates for the loss of SCHR transporters YwrB and YwrA in the Δ ywrBA B. subtilis strain.…”
Section: Discussionmentioning
confidence: 99%
“…The SCHR family comprises mono-domain proteins of around 200 aa in length, while the LCHR family consists of bi-domain proteins 400 aa long. Interestingly, certain strains encode a combination of mono- and bi-domain chromate transporters in their genomes, located either on the chromosome or a plasmid, with different contributions to overall chromate resistance, as in the case for Burkholderia xenovorans ( Reyes-Gallegos et al, 2016 ). All chromate transporters typically possess multiple transmembrane segments (TMS).…”
Section: Introductionmentioning
confidence: 99%
“…xenovorans LB400, which possesses six genes encoding chromate ion transporters, only the chrA2 gene present on a megaplasmid is subject to chromate-induced expression [ 35 ]. Interestingly, it was recently demonstrated that ChrA2 is the major determinant of chromate resistance in this organism [ 37 ]. The chrBACF operon of Ochrobactrum tritici 5bvl1, which is located in a chromosomally integrated transposon, proved also to be chromate-induced [ 38 ].…”
Section: Discussionmentioning
confidence: 99%